Central obesity, obesity, and physical activity among university staffs - Harikrishnan Ranganathan; Manjit Kaur Khaira; Raja Lexshimi Raja Gopal; Abid Hussain Bhat; Nabilah Ahmad; Siti Esah Bahari; Dina Adam; Kamalambal Harikrishnan (Intelektual Pustaka Media Utama, 2023)
Waist circumference (WC) is considered as a superior indicator to predict central obesity and its related comorbidities. Limited studies were conducted to infer central obesity using WC among university staffs. A cross-sectional study through the convenience sampling method was employed using the short form international physical activity questionnaire, anthropometric measurements, and WC measurement to infer a level of physical activity, body mass index (BMI), and central obesity. Seventy staff from three private universities in Malaysia participated in this study. There is a high prevalence (78.6%) of central obesity among the participants irrespective of their age. Majority of the participants fall under the overweight (37.1%) and obese (21.4%) category of BMI 48.6% reported to be involved in low level of physical activity. No difference in prevalence of central obesity based on age, gender, and level of physical activity. There is a moderately strong correlation between BMI and WC. In this study notably a high prevalence of central obesity in participants with underweight and desirable weight category of BMI was reported, which synergizes the concept of including WC measurement in health promotion activities. Appropriate multi- component and multi-level interventions can be considered to this population to prevent/combat obesity.